Kajian Potensi Pariwisata Perkotaan di Kota Malang Berdasarkan Stakeholder - Mirajanatin, Herlinda Pramesvari; Sutikno, Fauzul Rizal; Sari, Nindya (Jurnal Tata Kota dan Daerah, 2013)
The Role of stakeholders toward the development of tourism in Malang is not only to take decision for the tourism policy but also to manage the attraction of tourism in Malang. The problems being encountered are the number of tourists which is unstable, and also some existing tourism potencies which are managed inattentively. But then, Malang still has an urban tourism which needs role of stakeholders to manage the tourism. Therefore, it is conducted a study which aims to identify the strategy of urban tourism in Malang based on stakeholders. Analysis method of the study consists of overlaying the tourism sites, determining the evaluation criteria using Analytical Hierarchy Process; finding out several alternatives using SWOT and IFAS-EFAS, evaluating the alternatives using policy criteria recommendation, and deciding the alternatives using Goeller Scorecard. Based on the result of the study, the tourism strategies of Malang based on stakeholders can be formulated become: (a) to socialize the policy of every tourism attraction; (b) to determine the job division clearly between government and private enterprise; (c) to intertwine tourism attraction through holding events; (d) to develop the attraction with travel package tours, festivals, and fairs; (e) to improve and to keep facilities on every tourism places; (f) to allocate public transportation for the tour transportation (g) to increase the number of tourists by improving the quality of urban tourism; (h) to hold promotions using various media.Keywords: Tourism, Stakeholders.